DOI: 10.33015/dominican.edu/2018.bio.04
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemic Rickets

Abstract: Hypophosphatemic rickets is a rare, renal phosphate wasting disorder that presents various skeletal deformities. Although there are specific clinical presentations and biochemical findings used to identify hypophosphatemic rickets, there are various underlying renal phosphate wasting disorders that can lead to hypophosphatemic rickets making diagnosis extremely difficult. A targeted literature review through electronic search engines (e.g., BMC, PubMed, Google Scholar) was conducted to: 1) consolidate and summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…315 In pentameric ligand-gated ion channels such as nAChR 752,759,760 and GABAAR, 761 cholesterol molecules have been found to bind preferentially to the non-annular sites located at the inter-subunit interfaces. Similar nonannular cholesterol sites have been confirmed by various simulation techniques as well as free energy calculations in ABC transporters, including Pgp 339,762 and ABCG1. 753 Likewise, conserved cholesterol interaction sites have been uncovered in neurotransmitter sodium symporters (NSSs).…”
Section: Cholesterolsupporting
confidence: 63%
“…315 In pentameric ligand-gated ion channels such as nAChR 752,759,760 and GABAAR, 761 cholesterol molecules have been found to bind preferentially to the non-annular sites located at the inter-subunit interfaces. Similar nonannular cholesterol sites have been confirmed by various simulation techniques as well as free energy calculations in ABC transporters, including Pgp 339,762 and ABCG1. 753 Likewise, conserved cholesterol interaction sites have been uncovered in neurotransmitter sodium symporters (NSSs).…”
Section: Cholesterolsupporting
confidence: 63%
“…The results of other workers ( 4,6,8) suggest that the plants of the parental lines do not possess a pair of rye chromosomes in addition to the normal wheat complement. This mechanism should not be ruled out, however, because it is possible that the rye chromosome producing hairy neck may affect different strains of wheat to different degrees.…”
Section: Discussionmentioning
confidence: 81%
“…In comparisons of hairyneck with smooth-neck F 2 and Fa plants, the plants with hairy neck were significantly shorter. O'Mara ( 4,6) has reported that wheat plants monosomic or disomic for the hairy-neck rye chromosome were shorter than those of normal wheat. Oehler (7) also found that pubescent plants had shorter culms than non-pubescent individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sears, as reported by Shebeski and Wu ( 20), Red Egyptian has a factor for resistance to races 17 and 56 of stem rust on chromosome XX and another factor for resistance to stem rust races 38, 56, and 138 on chromosome VI. O'Mara ( 12) reported that Marquis wheat carries a strong awn…”
mentioning
confidence: 99%